Senam Lansia Menurunkan Tingkat Depresi Pada Lansia - Rahmawati Ramli; Suhermi Suhermi (FORIKES, 2021)
Exercise can be a cure for a variety of psychiatric symptoms, can reduce anxiety, depression, fatigue and confusion. Elderly gymnastics is a mild exercise that is easy to do and not burdensome, which can be applied to the elderly. This study aims to determine the effect of elderly exercise on decreasing levels of depression. The research design used was an experiment with a pre-experimental design that is one group pretest-posttest design. This study uses a nonrobability sampling technique with a purposive sampling approach. The study was conducted in the Pampang Health Center Work Area in January - June 2020. The study sample was 30 elderly people who met the sample criteria. The instrument of this study was to use a Yesavage Depression scale to be used on the pretest and posttest. Processing data using statistical tests paired sample T test. The results showed a difference in the average level of depression of the elderly before and after being given the elderly gymnastics. Elderly before being given gymnastics had an average depression level of 18.1 whereas after being given elderly exercise averaging 16.1. So it can be concluded if there is an influence (p value of 0.001) elderly exercise on the decrease in the level of depression in the elderly in the work area of Pampang Health Center. Therefore, the elderly should be encouraged to do physical activity in the form of elderly exercise in order to improve their health status and to avoid depression. Keywords: elderly; elderly gymnastics; depression ABSTRAK Olahraga dapat menjadi penyembuh untuk berbagai gejala kejiwaan, dapat mengurangi kekhawatiran, depresi, keletihan dan kebingungan. Senam lansia merupakan olahraga ringan yang mudah dilakukan dan tidak memberatkan, yang dapat diterapkan pada lansia. Penelitian ini bertujuan untuk mengetahui pengaruh senam lansia terhadap penurunan tingkat depresi. Desain penelitian yang digunakan yaitu eksperimen dengan rancangan pre eksperimen yaitu one group pretest-posttest design. Penelitian ini menggunakan teknik nonrobability sampling dengan pendekatan purposive sampling. Penelitian dilakukan di Wilayah Kerja Puskesmas Pampang pada bulan Januari - Juni 2020. Sampel penelitian adalah 30 Orang lansia yang memenuhi kriteria sampel. Instrumen Penelitian ini adalah menggunakan Alat ukur skala Depresi Yesavage untuk digunakan pada pretest dan posttest. Pengolahan data menggunakan uji statistik paired sample T test. Hasil penelitian menunjukkan adanya perbedaan rata-rata tingkat depresi lansia sebelum dan sesudah diberikan senam lansia. Lansia sebelum diberikan senam lansia memiliki tingkat depresi rata-rata 18,1 sedangkan setelah diberikan senam lansia rata-rata 16,1, sehingga disimpulkan terdapat pengaruh (nilai p 0,001) senam lansia terhadap penurunan tingkat depresi pada lansia di wilayah kerja Puskesmas Pampang. Lansia sebaiknya dianjurkan untuk melakukan aktifitas fisik berupa senam lansia ini agar meningkatkan status kesehatannya dan dapat terhindar dari depresi. Kata kunci: lansia; senam lansia; depresi